Dampak Alih Fungsi Lahan Hutan Menjadi Lahan Perkebunan Terhadap Kualitas Fisik Tanah: Impact of Forest Land Use Change to Plantation Land on Soil Physical Quality - Junedi, Heri; Antony, Dedy; Mastur, Agus Kurniawan (Jurnal Silva Tropika, 2025)
ABSTRACT The conversion of land from forest land to plantation land causes the surface of the land to be exposed for quite a long time. This results in rapid decomposition of organic matter so that the organic matter content in the soil decreases rapidly. As a result, there was a decline in physical quality. The research was descriptive exploratory, with a field survey approach using a 1:10,000 scale work map and supported by soil analysis in the laboratory. Representative areas were selected using the Stratified Random Sampling method for three types of land use, namely rubber plantations, oil palm plantations and shrubs. Each soil sample was taken randomly 3 times on a slope of 3-8%. Sampling was carried out at depths of 0-30 cm and 31-60 cm. The parameters observed in this research were soil texture (pipette method), soil structure (field observations), soil organic matter content (Walkley & Black method), soil volume weight (gravimetric method), porosity (based on calculations), soil permeability (De Boodt method), and available soil water content (Plate Apparatus-Gravimetric method). The research results show that the conversion of secondary forest land to plantation land has an impact on reducing organic matter content, soil porosity, soil permeability, and available soil water content and increasing soil volume weight. It is necessary to conduct further studies on the impact of land conversion on the quality of soil chemical properties and find solutions so that the decline in soil quality that has occurred is slowed.   Keywords: conversion, degradation, forest, physical quality   ABSTRAK Alih fungsi lahan dari lahan hutan menjadi lahan perkebunan menyebabkan terbukanya permukaan lahan dalam waktu yang cukup lama. Hal ini mengakibatkan terjadinya dekomposisi bahan organik secara cepat sehingga kandungan bahan organik di dalam tanah menurun secara cepat. Akibatnya terjadi penurunan kualitas fisik Penelitian bersifat deskriptif eksploratif, dengan pendekatan survei lapangan menggunakan peta kerja skala 1:10.000 dan didukung analisis tanah di laboratorium. Pemilihan area pewakil dengan menggunakan metode Stratafied Random Sampling pada tiga macam tipe penggunaan lahan yaitu lahan kebun karet, kebun kelapa sawit, dan semak belukar. Sampel tanah diambil masing-masing secara acak sebanyak 3 kali ulangan pada kemiringan lereng 3-8 %. Pengambilan sampel dilakukan pada kedalaman 0-30 cm dan 31-60 cm. Parameter yang diamati pada penelitian ini adalah tekstur tanah (metode pipet), struktur tanah (pengamatan di lapangan), kandungan bahan organik tanah (metode Walkley & Black), berat volume tanah (metode gravimetri), porositas (berdasarkan perhitungan), permeabilitas tanah (metode De Boodt), dan kadar air tanah tersedia (metode Plate Apparatus-Gravimetri). Hasil penelitian menunjukkan alih fungsi lahan hutan sekunder menjadi lahan perkebunan berdampak pada penurunan kandungan bahan organik, porositas tanah, permeabilitas tanah, dan kadar air tanah tersedia dan peningkatan berat volume tanah. Perlu dilakukan kajian lanjut dampak alih fungsi lahan terhadap kualitas sifat kimia tanah dan menemukan solusi agar penurunan kualitas tanah yang telah terjadi diperlambat.   Kata kunci: degradasi, hutan, konversi, kualitas fisik